Building Trust in Startup Communication Exploring the Interplay of Arguments and Stories in the Case of the Nikola Corporation - Born, Marius; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book explores the intriguing narrative of Nikola Corporation's startup journey in this insightful case study, examining its rapid ascent and subsequent decline from both a narrative and argumentative perspective. Founded by Trevor Milton, Nikola initially garnered investor interest with promises of a cleaner, sustainable alternative to diesel trucks. However, the company's surge in valuation was short-lived, as accusations from a short seller triggered a trust crisis, exposing alleged deception and raising doubts about the company's technology claims. This case study particularly focuses on the nuances of startup communication, emphasizing the critical importance of effective and trustworthy strategic communication for emerging tech ventures. It provides an in-depth look at the methods and tools necessary for startups to navigate initial skepticism and data limitations without exposing themselves to potential crises. Key insights include crafting compelling startup stories while maintaining trustworthiness, meeting investor information needs in an argumentatively convincing structure, recognizing the risks of blind faith in charismatic founders, and implementing internal checks and balances to safeguard against deception. Nikola's story serves as a cautionary tale, offering valuable lessons for entrepreneurs, investors, and scholars alike. This comprehensive examination sheds light on the challenges faced by startups dependent on emerging technologies and ambitious promises, making it an indispensable addition to the reading list of entrepreneurs.
Part I: Research Framework -- 1. Introduction -- 2. Literature Review -- 3. Analytical Framework -- Part II: Case Study$1 (BThe Rise and Fall of the Nikola Corporation -- 4. Case Introduction -- 5. Nikola$1 (Bs Rise -- 6. The Crisis Episode -- 7. The Hindenburg Report as a Turning Point -- Part Iii: Results, Discussion, And Conclusion -- 8. Findings and Evaluation -- 9. Limitations and Recommendations for Future Studies.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: New business enterprises; Venture capital; Communication in organizations; Communication; Information theory; Start-Ups and Venture Capital; Corporate Communication; Media and Communication Theory